Single cell sequencing revealed parathyroid oxyphil cells are involved in osteoporosis under primary hyperparathyroidism - Zhang, Xinguo; Bai, Ruifeng; Li, Minjuan; Li, Zhigang; Zhao, Xian; Cao, Renwei; Tan, Shen; Cheng, Kaiyuan; Zha, Yejun; Jiang, Xieyuan; Lu, Shuai (Frontiers in Endocrinology, 2025)
ObjectiveTo analyze the heterogeneity of parathyroid cells between patients with primary hyperparathyroidism (PHPT) osteoporosis and PHPT non-osteoporosis patients.MethodsResected parathyroid tissues were collected from PHPT patients of osteoporosis and non-osteoporosis. Single cell sequencing (SCS) to investigate cell types in parathyroid tissue involved in osteoporosis under PHPT. Further cell-cell interaction and communication, pseudotime trajectory analysis, sub-population analysis of parathyroid chief cells and parathyroid oxyphil cells, Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional prediction analysis to confirm specific function of parathyroid cells.ResultsHallmark-IL2/STAT5 and WNT/β-catenin pathways were upregulated in parathyroid cells of osteoporosis patients. Highest interactions and cell-cell communications were enriched in parathyroid cells. Subcluster analysis disclosed overall highest 31.86% CXCL10-PCC parathyroid chief cells, but SPARCL1-OC parathyroid oxyphil cells were higher in osteoporosis patients. Pseudotime trajectory analysis displayed that parathyroid oxyphil cells were in abundance in osteoporosis patients. In total, 281 DEGs involved in kinase activity were identified in osteoporosis patients. Heatmap showed HSPA1A-OC parathyroid oxyphil cells are predominantly involved in numerous and strongest cell interactions. GO and KEGG enrichment revealed PTH, NOTCH, FGF, EGF and CD59 pathways were significantly up-regulated in all parathyroid subpopulations in osteoporosis patients.ConclusionSingle cell sequencing revealed highest number of parathyroid cells in parathyroid tissue in patients suffering with PHPT osteoporosis. Parathyroid oxyphil cells are predominantly involved in osteoporosis under PHPT.